CORRELATION OF ANXIETY AND ACADEMIC PROCRASTINATION OF STUDENTS SMP NEGERI 17 BENGKULU CITY - Rahma Agustini Cahyani; Anni Suprapti; Mayang T. Afriwilda (UNIVERSITAS BENGKULU, 2023)
This study sought to define the nature of the relationship between student worry and academic procrastination. The sample for this research was 243 students of SMP Negeri 17 Bengkulu City, totaling 867 people using the Basic Random Selection technique. This research uses a quantitative descriptive research design with correlational techniques. The instruments used in this research were the academic procrastination questionnaire and the anxiety questionnaire. Product moment correlation is used to analyze the data. The research results show that there is a significant positive relationship between academic procrastination and anxiety, with a correlation coefficient of 0.419 at a significance level of 0.000 (p<0.05). This shows a positive correlation between academic procrastination and anxiety: the greater the anxiety, the higher the procrastination. Keywords: anxiety, academic procrastination, student